MODEL OF SISTER CITY COOPERATION IN ORDER TO IMPROVE REGIONAL DEVELOPMENT IN BANYUMAS REGENCY - Noer Indriyati; S Sanyoto; Aryuni Yuliantiningsih; Agus Mardianto; W Wismaningsih (Jurnal Dinamika Hukum, 2016)
The world has entered an era of openness, the nation that choose to close from international relations will be excluded from modern civilization. Sister city is the concept of coupling of two different cities and political administration with the aim of establishing relationships of cultural and social contact between people. This paper used statutory approach, with a qualitative analysis of the juridical. Cooperation with overseas regions are snowball, which mean begins with one thematic cooperation and can be resume in other fields. Sister city cooperation can increase foreign exchange thereby increasing regional development. Cooperation in the Regency of Banyumas has yet to be realized, and reach new level of offerings to the country's area contact.Keywords: Authority, Banyumas Regency, Sister City.